2020
DOI: 10.1186/s12933-020-01008-5
|View full text |Cite
|
Sign up to set email alerts
|

Triglyceride glucose index is an independent predictor for the progression of coronary artery calcification in the absence of heavy coronary artery calcification at baseline

Abstract: Background: Data on the relationship between the triglyceride glucose (TyG) index and coronary artery calcification (CAC) progression is limited. This longitudinal study evaluated the association of TyG index with CAC progression in asymptomatic adults. Methods:We enrolled 12,326 asymptomatic Korean adults who had at least two CAC evaluations. The TyG index was determined using ln (fasting triglycerides [mg/dL] × fasting glucose [mg/dL]/2). CAC progression was defined as a difference ≥ 2.5 between the square r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
95
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(102 citation statements)
references
References 42 publications
7
95
0
Order By: Relevance
“…Furthermore, Park et al [51] reported that TyG-index is an independent predictor of coronary artery calcification progression. Moreover, in a study conducted among South Korean adults, TyG-index was reported as an independent predictor of coronary artery calcification (CAC) progression; this issue was more prominent among adults without heavy CAC at baseline [52].…”
Section: Tyg-index and Cardiovascular Outcomesmentioning
confidence: 99%
“…Furthermore, Park et al [51] reported that TyG-index is an independent predictor of coronary artery calcification progression. Moreover, in a study conducted among South Korean adults, TyG-index was reported as an independent predictor of coronary artery calcification (CAC) progression; this issue was more prominent among adults without heavy CAC at baseline [52].…”
Section: Tyg-index and Cardiovascular Outcomesmentioning
confidence: 99%
“…Several studies have demonstrated that higher levels of TyG index were associated with an increased risk of arterial stiffness [22][23][24][25][26]. However, most of the studies were conducted in a relatively healthy population.…”
Section: Introductionmentioning
confidence: 99%
“…[16] Other studies demonstrated the TyG index was an independent predictor of coronary artery calci cation progression and risk of cardiovascular diseases. [8,17] In addition, previous studies suggested the TyG index predicted severity and outcomes in patients with acute coronary syndrome. [6,18,19] Wang et al reported the TyG index predicted future cardiovascular events in patients with diabetes and acute coronary syndrome independently of known cardiovascular risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…[5] Previous studies have indicated that the TyG index is associated with cardiovascular disease morbidity and mortality in the general population and different types of patient cohorts. [6][7][8][9] Lately, the TyG index has been proposed as a direct marker for the risk of incident ischemic stroke (IS) in general population. [10] To date, no relevant study has focused on the impact of the TyG index on mortality in patients with critically ill stroke including IS and hemorrhage stroke (HS).…”
Section: Introductionmentioning
confidence: 99%